Colouterine fistula secondary to pyometra: a case report - Moon Kyoung Cho; Tae Young Kim; Chul Hong Kim (Clinical and Experimental Obstetrics & Gynecology, 2021)
Pyometra is defined as the collection of purulent material in the uterine cavity. Colouterine fistula is a rare condition with less than 30 cases being reported in the literature. We believe this to be the first reported case of colouterine fistula secondary to pyometra. An 85-year-old woman with generalized abdominal pain and malodorous vaginal discharge for two weeks presented to the emergency room of Chonnam national university hospital. Physical examination confirmed the presence of the malodorous vaginal discharge. Abdominopelvic computed tomography scan demonstrated an abscess within the endometrial cavity and the presence of a fistula between the colon and the uterus. The patient underwent magnetic resonance imaging which revealed a communication between the distal sigmoid colon and the uterus. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, drainage of the abscess and a sigmoid colon resection were performed. Histopathological study of the surgical specimen revealed acute suppurative inflammation without evidence of malignancy.